2014
DOI: 10.1186/1472-6831-14-71
|View full text |Cite
|
Sign up to set email alerts
|

Panoramic radiography and cone-beam computed tomography findings in preoperative examination of impacted mandibular third molars

Abstract: BackgroundPreoperative radiographic examination of impacted mandibular third molars (IMTM) is essential to prevent inferior alveolar nerve injury during extraction. The purpose of this study was to evaluate the correlation between cone-beam computed tomography (CBCT) and digital panoramic radiography (DPR) findings in preoperative examination of IMTM.MethodsThis retrospective study included 298 teeth in 191 individuals. The relationship between the inferior alveolar canal (IAC) and the IMTM (buccal, lingual, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 38 publications
3
41
0
7
Order By: Relevance
“…This resembles the data reported by Tantanapornkul et al., who they studied 142 teeth and determined that the canal was inferior to 64 teeth (45%), lingual to 37 teeth (26%), buccal to 36 teeth (25%), and between the roots of five teeth (4%). In contrast, much of the literature has reported that the canal is most often buccal or lingual to the third molar. It is clear that there is significant anatomical variation in the position of the mandibular canal.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This resembles the data reported by Tantanapornkul et al., who they studied 142 teeth and determined that the canal was inferior to 64 teeth (45%), lingual to 37 teeth (26%), buccal to 36 teeth (25%), and between the roots of five teeth (4%). In contrast, much of the literature has reported that the canal is most often buccal or lingual to the third molar. It is clear that there is significant anatomical variation in the position of the mandibular canal.…”
Section: Discussionmentioning
confidence: 91%
“…Darkening, deflection, or narrowing of the roots of a third molar, as well as interruption, diversion, or narrowing of the white lines of the mandibular canal are associated with a higher risk of injury . The most common sign of a close relationship between these two structures has been consistently reported as the interruption of the white line, followed by darkening of the roots …”
Section: Introductionmentioning
confidence: 99%
“…It is recommended in this study to use CBCT as secondary diagnostic modality when panoramic radiograph Gomes et al 2008 Panoramic radiograph does not has a high diagnostic accuracy when it is used in the assessment of risk in surgical extractions of lower third molars Tantanapornkul et al 2007Ghaeminia et al 2011 The diagnostic accuracy of CBCT was superior to panoramic radiography in predicting neurovascular bundle exposure following assessment of the relationship of the third molar root tip to the IAC Hasegawa et al 2013 Panoramic findings mostly inconsistent (62.5%) to CBCT findings. Thus, in planning surgical removal of mandibular third molar, panoramic radiography alone does not provide sufficiently reliable images to assess the risk associated with nerve exposure Peker et al 2014 Less accuracy in panoramic radiograph may indicate further preoperative assessment of impacted mandibular third molar with CBCT especially when darkening of the roots and interruption of the white line are observed on panoramic images shows superimposition of the third molar root on the roof of IAC and the presence of root below the roof of the canal. Additional evaluation with CBCT in such cases is important to determine the actual risk associated with the inferior alveolar nerve injury following surgical removal of impacted mandibular third molar.…”
Section: Resultsmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) is a relatively new imaging modality. Compared with the conventional panoramic radiography (PAN), CBCT can reconstruct the three-dimensional images, provides better image of the teeth and their surrounding structures and thus gives the doctors a more detailed insight into the local anatomy of the teeth [5,6]. As a result, assisted with the CBCT images, the displaced IMTM could be located more accurately, and the removal will be expected to reduce the likely injury to the local structures.…”
Section: Introductionmentioning
confidence: 99%